Pengembangan Tes Pembelajaran Qawaid Arabiyah dengan Menggunakan Wordwall di Madrasah Tarbiyah Islamiyah Paninggahan (Taqdir, 2024)
Arabic teachers still use the traditional method of pencil and paper in conducting Arabic grammar tests. In addition, Arabic teachers do not apply Arabic grammar questions according to the level of difficulty (low, medium, and high). Researchers see the importance of developing an Arabic grammar learning test using the Wordwall application that suits the needs of students and is able to measure students' abilities comprehensively, both at low, medium and high levels. This research uses the 4D approach.. The data to be analyzed are quantitative and qualitative data derived from experts, teachers, and students. Data were collected from questionnaires and tests. The results of this development research are 1) Designing a test for teaching Arabic grammar by using Wordwall in Madrasah Tarbiyah Isamiyah Paninggahan Solok: First, analyzing the curriculum, analyzing student books, analyzing the form of the test, analyzing the needs of Arabic teachers and students, and second, designing the test by writing a grid of questions, writing questions in the test instrument, writing answer keys, writing questionnaires, and validators in terms of Arabic language, evaluation, and media, and reviewed by these experts. 2) Production of Arabic grammar teaching test using Wordwall at Madrasah Tarbiyah Isamiyah Paninggahan Solok, where 30 multiple choice questions and description questions with varying difficulty levels ranging from C1-C4, then the first product was tested on 16 students. After that, student and teacher responses to show its effectiveness or practicality. 3) The use of word wall application in the experimental class was good enough for the implementation of Arabic grammar test in tenth grade at Madrasah Tarbiyah Isamiyah Paninggahan Solok. The high scores of students in the experimental class were better than the control class, before the experimental class, the test result of 46 was rated “weak” and after the experimental class, the test result of 77 was rated “very good” and confirmed with the result that t = 14.005 > t = 1.753.